Tocilizumab and liver injury in patients with COVID-19. (October 2020) - Serviddio, Gaetano; Villani, Rosanna; Stallone, Giovanni; Scioscia, Giulia; Foschino-Barbaro, Maria Pia; Lacedonia, Donato
Current mortality rate in patients with COVID-19 disease is about 2%, whereas 5% of patients require admission to the intensive care unit. It is assumed that interleukin (IL)-6 may be involved in the pathogenesis of severe COVID-19 infections; therefore, in the absence of a specific antiviral therapy, some authors have suggested that tocilizumab – a drug used to block the signal transduction pathway of IL-6 – could have beneficial effects in the management of severe COVID-19 disease. However, mild-to-moderate elevation in transaminases and drug-induced liver injury have been observed in patients treated with tocilizumab. We present seven cases of patients with elevated liver enzymes [up to five times the upper limit of normal (ULN)] at baseline who received tocilizumab for life-threatening COVID-19 disease. All patients had no history of liver or pulmonary disease and were admitted for acute hypoxemic respiratory failure, dyspnea and fever due to COVID-19 bilateral pneumonia. IL-6 was available in six patients, and was significantly increased particularly in those with severe impairment of lung function. All patients received tocilizumab (8 mg/kg/day) for two consecutive days because of lack of improvement after hydroxychloroquine, azithromycin and lopinavir/ritonavir treatment. After tocilizumab administration, clinical condition rapidly improved and liver function test normalized within 3 weeks of treatment. Tocilizumab may be effective for the treatment of severe COVID-19 disease, even in patients with elevated liver function tests. Further studies are needed to evaluate the impact of tocilizumab use on liver function tests in patients with pre-existing chronic liver disease.